Targeted Suppression of miRNA-33 Using pHLIP Improves Atherosclerosis Regression. Issue 1 (10th May 2022) - Zhang, Xinbo; Rotllan, Noemi; Canfrán-Duque, Alberto; Sun, Jonathan; Toczek, Jakub; Moshnikova, Anna; Malik, Shipra; Price, Nathan L.; Araldi, Elisa; Zhong, Wen; Sadeghi, Mehran M.; Andreev, Oleg A.; et al.
Abstract : Background: miRNA therapeutics have gained attention during the past decade. These oligonucleotide treatments can modulate the expression of miRNAs in vivo and could be used to correct the imbalance of gene expression found in human diseases such as obesity, metabolic syndrome, and atherosclerosis. The in vivo efficacy of current anti-miRNA technologies hindered by physiological and cellular barriers to delivery into targeted cells and the nature of miRNAs that allows one to target an entire pathway that may lead to deleterious off-target effects. For these reasons, novel targeted delivery systems to inhibit miRNAs in specific tissues will be important for developing effective therapeutic strategies for numerous diseases including atherosclerosis. Methods: We used pH low-insertion peptide (pHLIP) constructs as vehicles to deliver microRNA-33-5p (miR-33) antisense oligonucleotides to atherosclerotic plaques. Immunohistochemistry and histology analysis was performed to assess the efficacy of miR-33 silencing in atherosclerotic lesions. We also assessed how miR-33 inhibition affects gene expression in monocytes/macrophages by single-cell RNA transcriptomics. Results: The anti-miR-33 conjugated pHLIP constructs are preferentially delivered to atherosclerotic plaque macrophages. The inhibition of miR-33 using pHLIP-directed macrophage targeting improves atherosclerosis regression by increasing collagen content and decreased lipid accumulation within vascular lesions. Single-cell RNA sequencing analysis revealed higher expression of fibrotic genes ( Col2a1, Col3a1, Col1a2, Fn1, etc) and tissue inhibitor of metalloproteinase 3 ( Timp3 ) and downregulation of Mmp12 in macrophages from atherosclerotic lesions targeted by pHLIP-anti-miR-33. Conclusions: This study provides proof of principle for the application of pHLIP for treating advanced atherosclerosis via pharmacological inhibition of miR-33 in macrophages that avoid the deleterious effects in other metabolic tissues. This may open new therapeutic opportunities for atherosclerosis-associated cardiovascular diseases via selective delivery of other protective miRNAs.